Financial analysis indicators and their impact on investment decision-making: for the national insurance company (applied research) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The financial analysis of the published financial statements is the means that enables businessmen, financial institutions, financial analysts and others to conduct their studies and conclusions to obtain information that helps them in the decision-making process, including decisions related to investment. National in making the decision on the investment activity, for the period from 2012 to 2018, through the information provided by the annual financial statements, by selecting a set of indicators provided by the financial statements, namely (liquidity ratio, activity percentage, profitability ratios) to measure the extent of this ability Indicators in determining their role in making an investment decision.